1988
DOI: 10.1017/s0033583500005011
|View full text |Cite
|
Sign up to set email alerts
|

Electric linear dichroism and birefringence of biological polyelectrolytes

Abstract: The phenomenon of electro-optic orientation was discovered by John Kerr in 1875 and has been used extensively for determining the optical polarizability anisotropy of small molecules and for high-speed transmission of optical signals. Measurements on biopolymers have been made at least since 1950, but only in the last decade have these yielded definitive structural and physical information. In the course of this review, it should become obvious that among the reasons for this late development is the inherent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 210 publications
(244 reference statements)
0
44
0
Order By: Relevance
“…bril component has the radially averaged B-DNA axis parallel to it and the (optically) uniaxial nature for unit cell, 12 are in accord, the chief polarizability of B-DNA being normal to the helix axis. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bril component has the radially averaged B-DNA axis parallel to it and the (optically) uniaxial nature for unit cell, 12 are in accord, the chief polarizability of B-DNA being normal to the helix axis. 14 …”
Section: Discussionmentioning
confidence: 99%
“…type I (D-1501), a preparation prepared from calf The persistence length for random B-DNA dethymus gland (CT-DNA) and lyophilized from a termined in solution from a number of studies buffered solution by the manufacturer to yield a using light scattering and electric dichroism is apfibrous preparation which contains residual bufproximately 500 Å (or 150 base pairs) 14 but it fer salt and 5% NaCl. In vivo the molecular weight increases at low ionic strengths (10-20 mM) to should approach 2.8 billion g/mol for a DNA macca.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental measurements indicated that the bases are oriented at 72" or less with respect to the helix axis direction (Charney, 1988). Moreover the larger ELD amplitude of the bound chromophores also arises from a local stiffening of the DNA around the intercalation sites (Herzyk et al, 1992).…”
Section: Intercalating Agentsmentioning
confidence: 99%
“…Equation [11] shows that the relaxation time τ 1 is very sensitive to the diameter (2b) of a thin disklike particle of a fixed thickness of 2a. For example, a 1.5-fold increase of the diameter corresponds to a 3.37-fold increase in the relaxation time.…”
Section: Decay Signal and Field-off Relaxation Timementioning
confidence: 99%